Low HIF-1 alpha and low EGFR mRNA Expression Significantly Associate with Poor Survival in Soft Tissue Sarcoma Patients; the Proteins React Differently - Rot, Swetlana; Taubert, Helge; Bache, Matthias; Greither, Thomas; Wuerl, Peter; Holzhausen, Hans-Juergen; Eckert, Alexander W.; Vordermark, Dirk; Kappler, Matthias (International Journal of Molecular Sciences, 2018)
In various tumors, the hypoxia inducible factor-1 alpha (HIF-1 alpha) and the epidermal growth factor-receptor (EGFR) have an impact on survival. Nevertheless, the prognostic impact of both markers for soft tissue sarcoma (STS) is not well studied. We examined 114 frozen tumor samples from adult soft tissue sarcoma patients and 19 frozen normal tissue samples. The mRNA levels of HIF-1 alpha, EGFR, and the reference gene hypoxanthine phosphoribosyltransferase (HPRT) were quantified using a multiplex qPCR technique. In addition, levels of EGFR or HIF-1 alpha protein were determined from 74 corresponding protein samples using ELISA techniques. Our analysis showed that a low level of HIF-1 alpha or EGFR mRNA (respectively, relative risk (RR) = 2.8; p = 0.001 and RR = 1.9; p = 0.04; multivariate Cox ' s regression analysis) is significantly associated with a poor prognosis in STS patients. The combination of both mRNAs in a multivariate Cox's regression analysis resulted in an increased risk of early tumor-specific death of patients (RR = 3.1, p = 0.003) when both mRNA levels in the tumors were low. The EGFR protein level had no association with the survival of the patient's cohort studied, and a higher level of HIF-1 alpha protein associated only with a trend to significance (multivariate Cox's regression analysis) to a poor prognosis in STS patients (RR = 1.9, p = 0.09). However, patients with low levels of HIF-1 alpha protein and a high content of EGFR protein in the tumor had a three-fold better survival compared to patients without such constellation regarding the protein level of HIF-1 alpha and EGFR. In a bivariate two-sided Spearman's rank correlation, a significant correlation between the expression of HIF-1 alpha mRNA and expression of EGFR mRNA (p < 0.001) or EGFR protein (p = 0.001) was found, additionally, EGFR mRNA correlated with EGFR protein level (p < 0.001). Our results show that low levels of HIF-1 alpha mRNA or EGFR mRNA are negative independent prognostic markers for STS patients, especially after combination of both parameters. The protein levels showed a different effect on the prognosis. In addition, our analysis suggests a possible association between HIF-1 and EGFR expression in STS.
EVALuna2:35875